Cementless vs Cemented Total Ankle Arthroplasty: A Prospective Comparison of the Laterally Placed Trabecular Metal Ankle. Issue 4 (16th October 2019) - Younger, Alastair S.E.; Usuelli, Federico G.; Bohay, Donald; Krause, Fabian; Giza, Eric; Patsalis, Theo; Parekh, Selene G.; Raikin, Steve; Ellington, Kent
Category: Ankle, Ankle Arthritis Introduction/Purpose: The laterally placed trabecular metal ankle replacement is placed using a jig and a fibular osteotomy. The tibia and talus are reamed to match the curved contour of the replacement. Additional fixation is achieved using two rails on the tibial and talar component. Additional cement fixation can be used by a bead of cement on the rail to assist in early component fixation. Cement fixation did not cover the entire ingrowth surface but was only used on the rails as per the technique manual. The purpose of this study is to compare the early results of 113 total ankle replacements with and without rail cement. Methods: 121 patients were enrolled in a prospective study. 10 centers were involved. 3 patients underwent revision and 5 withdrew (1 death, 2 lost to follow up and 2 requested discontinuation). Patients were assigned cement or no cement based on the surgeons practice. EQ5D, AOFAS, AOS scores were obtained preoperatively and at 6 weeks, 6 months, and yearly thereafter. Revision of metal components for infection or loosening were secondary end points. Statistical significance was tested by the Wilcoxon Signed Rank Test 26 and set at p= 0.05. 95% confidence intervals are given. 59 ankles had cement, and 53 had press fit. The demographics showed the cement augmentation patients were heavier and older. The cement cases had longer surgical times (169 minutes, CI 159 to 179 vs 154, CI 144 to 163). Of 113 cases, 113 were followed at 1 year, and 100 at 2 years and 67 at 3 years. Results: The press fit components without cement showed statistically better outcomes at 6 weeks for the AOFAS score. The EQ5D favored the press fit component at 6 weeks, 6 months and 1 year. For the AOS pain scale the 6 month results favored the press fit component, and for the difficulty scale the results favored the press fit components at 6 weeks and 1 year. Survivorship for all joint replacements (revision of metal components) was 96 percent for the total cohort, with 2 metal components in two ankles being revised, both in the cementless group (chi square not significant). Conclusion: As all outcomes to date favor press fit fixation there does not seem to be any need to augment fixation with cement in this total ankle design. There were two metal component revisions in the cementless group and one associated with loosening. There major are demographic differences between the groups and so an RCT would be required to correctly answer the question.